Comparison of shear ultrasonic results of electrolyte-acetamide molten mixtures - R. PŁOWIEC; G. BERCHIESI (Archives of Acoustics)
Shear ultrasonic investigation are presented in sodium trifluoroacetate/CF3COONa/-acetamide molten mixtures as a function of amide concentration. This results are compared with other electrolyte-acetamide molten mixtures investigated previously.